Efficacy and Safety of Treating Stage 2 Systolic Hypertension With Olmesartan and Olmesartan/HCTZ: Results of an Open‐Label Titration Study - Izzo, Joseph L. (J Clin Hypertens (Greenwich), 2007)
This study investigated an aggressive treatment program for stage 2 systolic hypertension (pretreatment systolic blood pressure [SBP] ≥160 mm Hg) using the angiotensin receptor blocker olmesartan medoxomil (OM) and hydrochlorothiazide (HCTZ). In this open‐label, 16‐week trial, 170 subjects received OM 20 mg/d for 3 weeks. If seated SBP/diastolic BP remained ≥120/80 mm Hg, subjects were advanced to successive 3‐week courses of OM 40 mg/d, OM/HCTZ 40/12.5 mg/d, and OM/HCTZ 40/25 mg/d. OM 20 mg/d reduced mean SBP by 16.9 mm Hg (P<.001), and there were further dose‐dependent decreases in mean SBP to a maximum of 34.5 mm Hg with OM/HCTZ 40/25 mg/d. At study end, 75.1% of subjects achieved SBP goal (<140 mm Hg) and 16.0% achieved SBP normalization (<120 mm Hg). Treatment was well tolerated at all doses. The addition of HCTZ did not change serum potassium levels but resulted in a dose‐independent but not symptomatic increase in serum glucose and uric acid. The authors conclude that an OM‐based regimen, with or without HCTZ in conventional doses, is effective in controlling and normalizing BP in stage 2 systolic hypertension.